Memória documental do Festival Internacional de Inverno da UFSM e da Semana Cultural Italiana de Vale Vêneto (RS) - Pivetta, Ana Lúcia Faccin (2020)
This research presents the study of preservation aiming to disseminate the documentary memory of the collection of the International Winter Festival of UFSM and the Italian Cultural Week of Vale Veneto, which is in the custody of the Museum of the Italian Immigrant Eduardo Marcuzzo, in the district of Vale Veneto, belonging to the municipality of São João do Polêsine (RS). Given the relevance for UFSM and Vale Veneto of these events, which have been going on for more than three decades, it is intended, based on the precepts of archival theory, to seek the preservation and dissemination of this documentary collection, in order to maintain memory and cultural identity of these events that intends to provide musical improvement for UFSM students and significant cultural, social and economic development for the region of the Fourth Colony of Italian Immigrants. In addition to the preservation of documentary memory based on archival theory and the consequent discussion and analysis of this collection, interviews were conducted with people involved in the organization and participation of these events, in order to bring new contributions to the documentation already existing at the Museum of the Italian Immigrant. Finally, in order to promote the dissemination of this documentary memory, a booklet was created with the aim of giving greater visibility to the general and specialized public, as well as serving as a source of research.